The Effect of Training and Managerial Activities on Employee Performance at PT. Bandung Berkah Alami Factory, West Java - Ricardo Manarintar Simarmata (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
The purpose of this study was to determine and examine the effect of providing training from the company and managerial activities on the performance of employees of the PT Bandung Berkah Abadi Factory. The population in this study were 54 field employees who worked at the PT Bandung Berkah Abadi Factory. The sampling method used saturated sampling technique which resulted in 54 employees. The research method used is descriptive analysis and multiple linear regression with a significant level of 0.05 through the t-test (partial), F-test (simultaneous) and determinant identification test (R2). The results of the F test show that there is a positive and significant effect on training variables and managerial activities on employee performance variables. The t-test results show that the training variable has a positive and significant effect on the employee performance variable. The results of the determinant identification test (R2) show that there is a close relationship between the training variable and the managerial activity variable on employee performance. Other factors outside this study such as direct financial and nonfinancial compensation and organizational commitment.